Assessment of Potential Risk Factors for the Development of Persistent Postural-Perceptual Dizziness: A Case-Control Pilot Study - Trinidade, Aaron; Harman, Paula; Stone, Jon; Staab, Jeffrey P.; Goebel, Joel A. (Frontiers in Neurology, 2021)
OBJECTIVES: (1) To assess whether neuroticism, state anxiety, and body vigilance are higher in patients with persistent postural-perceptual dizziness (PPPD) compared to a recovered vestibular patient group and a non-dizzy patient group; (2) To gather pilot data on illness perceptions of patients with PPPD. MATERIALS AND METHODS: 15 cases with PPPD and two control groups: (1) recovered vestibular patients (n=12) and (2) non-dizzy patients (no previous vestibular insult, n=12). Main outcome measures: Scores from the Big Five Inventory (BFI) of personality traits, Generalised Anxiety Disorder – 7 (GAD-7) scale, Body Vigilance Scale (BVS), Dizziness Handicap Inventory (DHI), modified Vertigo Symptom Scale (VSS) and Brief Illness Perception Questionnaire (BIPQ). RESULTS: Compared to non-dizzy patients, PPPD cases had higher neuroticism (p=0.02), higher introversion (p=0.008), lower conscientiousness (p=0.03) and higher anxiety (p=0.02). There were no differences between PPPD cases and recovered vestibular patients in BFI and GAD-7. PPPD cases had higher body vigilance to dizziness than both control groups and their illness perceptions indicated higher levels of threat than recovered vestibular patients. CONCLUSION: PPPD patients showed statistically significant differences to non-dizzy patients, but not recovered vestibular controls in areas such as neuroticism and anxiety. Body vigilance was increased in PPPD patients when compared with both recovered vestibular and non-dizzy patient groups. PPPD patients also exhibited elements of negative illness perception suggesting that this may be the key element driving the development of PPPD. Large scale studies focusing on this area in the early stages following vestibular insult are needed.